2018
DOI: 10.1007/s00392-018-1358-4
|View full text |Cite
|
Sign up to set email alerts
|

Extended ECG monitoring with an implantable loop recorder in patients with cryptogenic stroke: time schedule, reasons for explantation and incidental findings (results from the TRACK-AF trial)

Abstract: Registered at ClinicalTrials.gov: NCT02641678.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…A pooled analysis of published single arm studies demonstrated that the rate of detected AF increases with the duration of monitoring, from about 8.9% at 1 month to 17.9% at 6 months, 22.3% at 12 months and 25.2% at 36 months (Figures 3–6). 2473…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A pooled analysis of published single arm studies demonstrated that the rate of detected AF increases with the duration of monitoring, from about 8.9% at 1 month to 17.9% at 6 months, 22.3% at 12 months and 25.2% at 36 months (Figures 3–6). 2473…”
Section: Resultsmentioning
confidence: 99%
“…For ESUS patients, the pooled rate was 13.5% (95% CI 6.5–22.6), and globally, the AF detection with non-implantable devices was 12.3% (95% CI 9.4–15.4). 32,33,36,39,4346,4854,5667,69,70,100…”
Section: Resultsmentioning
confidence: 99%
“…However, we are convinced that the observational data currently available is promising and may even allow prediction of atrial fibrillation before it is detected. While the current analysis merely focuses on incidental findings during long-term follow-up of patients with implantable loop recorders [2], a previous study displayed a strong correlation between detection of supraventricular premature beats and short atrial runs and the later registration of atrial fibrillation in the same patient cohort [3]. The results of such analyses imply that current risk stratification in patients with cryptogenic stroke is not yet sufficient and the information offered by implantable loop recorders may significantly improve this.…”
Section: Sirsmentioning
confidence: 89%
“…We read with interest the recent paper published in Clinical Research in Cardiology on ECG monitoring with implantable loop recorder (ILR) in patients with cryptogenic stroke-retrospective analysis of TRACK AF study [1]. Authors demonstrated detection of atrial fibrillation (AF) in 19.1% of patients with cryptogenic stroke after median time of 10.7 ± 11.4 months.…”
Section: Sirsmentioning
confidence: 99%